Hidden Gem for Tourist in Central Part of Bali : Kehen Temple in Bangli - I Gede Mas Suputra (Bali Tourism Journal, 2022)
Tourist visits drastically fell for several months in Kehen Temple, as The Bangli Regency Tourism and Culture Office reported. From January-May 2021, the number of tourist visits to tourist objects and attractions in Bangli Regency reached 57,417, dominated by foreigners. However, there was nil visitor to the temple. Before the COVID-19 pandemic, tourism objects and attractions in Bangli Regency were packed with tourists from July to August. The most exceptional temple in Bangli, Kehen Temple, is a museum in disguise that display ancient remnants of old Balinese culture. The researcher presumed the shrine was established between the late IX century and early X century, according to the Kehen temple's copper inscriptions. During the reign of King Anak Wungsu, the place was the location for the inauguration ceremony for the royal officer. The event was held in the presence of the Hyang Kehen, a spiritual entity believed to be the Lord of Fire. In the 14th century, a priest from Java, Danghyang Nirartha, redesigned the site without losing its authenticity. Nirartha introduced the latest architectural landscape that is generally used by most of the temples in Bali. Kehen Temple has been developed as a tourist attraction with fully supported amenities, facilities, and access. In Kehen Temple, the visitor may directly witness the architectural design of the temple's entrance, the standout point that makes the temple exceptional. Then, various relics from the megalithic period and a sacred banyan tree in the temple courtyard.